Rethinking retrofit of residential heritage buildings. Issue 1 (14th June 2021) - Wise, Freya; Moncaster, Alice; Jones, Derek
What are the opportunities and challenges for upscaling the energy retrofit of heritage buildings? Heritage buildings comprise approximately 20% of the UK building stock and are challenging to retrofit sensitively because of their heritage values and traditional construction. These buildings may therefore be unconducive to standard retrofitting approaches. Twelve case studies in the UK are examined. Three key findings are presented together with their implications for upscaling retrofit. First, heritage residents are found to engage in positive energy behaviours, which differ from standard assumptions and have a significant impact on energy demand. Second, standard energy models are shown to considerably overestimate the energy use within heritage buildings, failing to accurately portray both traditional construction and residents' behaviours. Third, residents consider many common retrofits, such as replacement windows and wall insulation, to be unacceptable to their heritage values. A number of more acceptable and less invasive 'soft retrofits' were modelled and shown to have significant potential for reducing energy and carbon. Therefore, a more holistic approach to heritage building retrofitting needs to be taken, treating the complex interrelationship of buildings and their users as a system, and expanding notions of retrofitting to include soft retrofits and user behaviour. Policy relevance: This research identified the importance of appropriately retrofitting heritage buildings, which include around 20% of the UK building stock. Standard solutions such as wall insulation and window replacement are unlikely to be enacted by most heritage residents because they are not acceptable to their heritage values, suggesting the need to prioritise other measures. Standard energy models such as Reduced data Standard Assessment Procedure (RdSAP) were found to be inaccurate for heritage buildings, overestimating energy use by both buildings and occupants, and should not be used to inform retrofit decisions for these buildings. Notions of retrofit should be expanded beyond fabric alterations to include behavioural changes and non-technical measures, including thermal curtains or shutters, which are more acceptable to residents and therefore more likely to be actioned. The potential exists to upscale retrofitting in heritage buildings, but approaches must consider specific user behaviour and view buildings and their occupants as interconnected systems.